ROLE OF SUSTAINED-RELEASE CALCIUM ANTAGONIST (AMLODIPINE MALEATE) IN THE TREATMENT OF ESSENTIAL HYPERTENSION IN PATIENTS WITH ASTHMA - N. A. Karoli; A. A. Roshchina; A. P. Rebrov (Klinicist)
Objective: to evaluate the efficacy, vasoprotective properties, and safety of amlodipine maleate used in patients with asthma concurrent withessential hypertension (EH).Subjects and methods. Twenty asthmatic patients in remission with grade I–II EH were examined. The patients were given amlodipine maleate (Stamlo® M, Dr. Reddy’s Laboratories) in a daily dose of 5–10 mg for an antihypertensive purpose. External respiration tests, 24-hour blood pressure monitoring, and studies of endothelial vasomotor function and arterial elastic properties were performed in patients at baseline and after a 6-month course of therapy.Results. The good tolerability and safety of amlodipine maleate were ascertained in patients with asthma concurrent with EH, irrespective of the severity of bronchoobstructive syndrome and the degree of asthma control. These trials demonstrate not only the obvious antihypertensive effects of amlodipine maleate, but also its vasoprotective properties: its beneficial effect on endothelial vasoregulatory function and vascular wall rigidity.Conclusion. The findings confirm that it is expedient to use Stamlo® M in patients with asthma concurrent with EH.